Efeitos do p-cimeno e do alfa-pineno sobre a resposta inflamatória aguda - Kummer, Raquel (2015)
Inflammation is the first defense of the human organism against tissue injuries. Plants are important sources of bioactive substances and part of its biological activities are attributed to the essential oils. The monoterpenes are the main constituents of the essential oils and have many biological effects. The aim of this study was to evaluate the anti-inflammatory effects of p-cymene and alpha-pinene, plant-derived monoterpene. Therefore, it was evaluated the cytotoxicity by MTT test, acute toxicity in animal models, in vitro neutrophil chemotaxis, in vivo cell migration by peritonitis and mesenteric microcirculation carrageenan-induced. The effects of p-cymene was also evaluated on the phagocytosis ability of the macrophages and cytokine levels. In the cell viability assay, p-cymene and alpha-pinene showed low cytotoxicity (until 90 μg/mL) and absence of acute toxicity at doses up to 3g/Kg. The p-cymene (3, 10, 30, 60 μg/mL) reduced neutrophil migration toward fMLP; decreased the infiltration of total and polymorphonuclear leukocytes into peritoneal cavity (100, 200 and 400 mg/Kg); decreased the number of rolling (100, 200 mg/kg) and adherent leukocytes (100, 200, 400 mg/kg) to the perivascular tissue; increased the macrophage phagocytic index and reduced TNF-α levels. The alpha-pinene (1, 3, 10, 30 g/ml) reduced neutrophil migration toward fMLP and LTB4 stimulation; decreased the infiltration of total and polymorphonuclear leukocytes into peritoneal cavity (200 and 400 mg/Kg) and decreased the number of rolling and adherent leukocytes (200 and 400 mg/Kg) to the perivascular tissue. Our results showed evidences that p-cymene and alpha-pinene have anti-inflammatory effects and may be considered as promising drugs for treatment of inflammatory process with excessive leukocyte migration; however, more studies are needed to elucidate the mechanism action of these monoterpenes.